PENGEMBANGAN POTENSI DESA KEBONAGUNG, KABUPATEN GRESIK MELAUI SOSIALISASI DAN PELATIHAN PENGOLAHAN JERUK - Muhammad Syihabuddin; Alfah Anis Zaidah; Luthfi Nurul Huda (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
Kebonagung Village, Gresik Regency has extraordinary natural potential. The fertile soil makes Kebonagung one of the centers for producing quality limes. However, due to various reasons, such as the outbreak of the Covid-19 pandemic, sales of limes have decreased. That’s why, adaptations are needed so the sustainability of this potential is maintained. One alternative is to conduct socialization and training on lime processing for the community. This processing involves many elements of society, such as farmers, village governments, and Village-Owned Enterprises (BUMDes). BUMDes has an important role in maximizing the marketing of community products. This training processes limes into high-value products such as syrup, ice cream, and soap. In addition to reducing the waste generated from unsold limes, this also increases the selling value of products made by the community. The enthusiasm of PKK members was also seen. The PKK women (Family Welfare Empowerment) want to make the experiment done by the students of KKN (Community Service Program) of UIN Sunan Kalijaga Yogyakarta into one of the village products worthy of being marketed. Community involvement is important so the community is not only an object in empowerment but also becomes a subject in this empowerment program.